Dissociation of doubly charged Coronene as a function of internal energy. (July 2015) - Brédy, R; Ortéga, C; Ji, M; Chen, L; Bernard, J; Martin, S
Synopsis: We report on the dissociation of doubly charged Coronene ( C 24 H 12 2+ ) as a function of internal energy. The mass spectra were obtained for internal energy measured up to 50 eV using the CIDEC method in collisions with F + and H + at 3 keV. The dehydrogenation processes of the molecule were observed over this large range of energy as well as the other weaker channels, loss of C 2 H n, 2 C 2 H n and ionization. The branching ratios for the fragments C 24 H 12- n 2+, C 22 H 12- n 2+, C 20 H12- n 2+ and C 24 H12- n 3+ (n=0-6) were measured.